PENGARUH KEPUASAN PELANGGAN BISNIS BERBASIS ONLINE DAN KEPERCAYAAN PELANGGAN TERHADAP LOYALITAS PELANGGAN BOUGAINVILEA PADA MASA PANDEMI COVID-19 - Jamal, Fauziyah Nur; Fahmi, Afiqoh Akmalia; Rohmah, Wafrotur (Program Studi Manajemen, 2022)
Currently, the development of the Indonesian fashion world, especially in Yogyakarta, is growing rapidly, even though during the Covid-19 pandemic, online-based businesses actually grew rapidly. One of the e-commerce businesses involved is Bougainvilea. With an online sales concept, Bougainvilea provides a wide variety of the best products for the latest Muslim fashion. With the strength of its customers, this study aims to highlight the problem of how customer satisfaction and trust affect customer loyalty in e-commerce in Bougainvilea companies. Data was collected by means of a questionnaire to 195 respondents with a simple random sampling technique. Data analysis was carried out using a quantitative method using SmartPLS software. The results of the study identified that customer satisfaction has a positive and significant effect on customer loyalty, customer trust has a positive and significant effect on customer loyalty and customer satisfaction has a positive and significant effect on customer trust